Fecal Halitosis: A Case Report - Biswas, Suttam Kumar; Roy, Shilpi Rani; Paul, Arup Roton (Community Based Medical Journal, 2017)
There are many causes of fecal halitosis like poor oral hygene, bowel obstruction, GERD, oral malignancy, liver failure etc. Gastrocolic fistula is a rare cause of fecal halitosis. Gastrocolic fistula is a rare complication of adenocarcinoma of the colon. Despite radical resections, these patients usually have a poor prognosis with a mean survival of 23 months and long-term survival is rarely reported. A 40-year-old man of Netrokona district presented with diffuse abdominal pain, vomiting, fecal smell from mouth and weight loss for 3 months. A Barium enema revealed fistulous communication in between left colic flexure upto body of the stomach. Upper gastrointestinal tract endoscopy done repeatedly but report was normal. Colonoscopic report was a growth seen at 60 cm from anal verge and the scope couldn't be passed up. Histopathological report of colonoscopic biopsy was non specific chronic colitis. His part of colon, sleeve resection of stomach were resected en bloc. As per histopathological report, sections from the transvers colon tumor revealed an adenocarcinoma composed of malignant glands with an infiltrative pattern. Adjuvant chemotherapy with capecitabine and oxaliplatin was administered after surgery. Our patient is alive. En bloc resection with adjuvant chemotherapy offers the best treatment option for gastrocolic fistulas. This is one of the patients with greater survival reported in the medical literature. CBMJ 2017 January: Vol. 06 No. 01 P: 34-38